Design, implementation, and evaluation of PINDAR, a novel short program on GCP for academic medical center principal investigators conducting human subject research. Issue 6 (14th May 2019) - Plottel, Claudia S.; Mannon, Lois; More, Frederick G.; Katz, Stuart D.; Hochman, Judith S.
Abstract: TheP rincipalIN vestigatorD evelopment andR esources (PINDAR) program was developed at the NYU-H+H Clinical and Translational Science Award (CTSA) hub in response to a perceived need for focused good clinical practice (GCP) training designed specifically for principal investigators (PIs) performing human subject research. PINDAR is a novel 6-hour, instructor lead, participatory, in-person course for PIs developed de novo, piloted, and implemented. One hundred and seventeen faculty PIs participated in PINDAR from November 2016 through September 2018. All obtained mutual recognition for ICH E6 GCP training from TransCelerate Biopharma . PINDAR was well received by participant PIs, and feedback surveys have revealed a high degree of satisfaction with the program. Other CTSA hubs and research-intensive health systems should consider adopting a similar course focused on GCP for PIs.